Land titles and farmers' perceptions about ease of conducting transactions: a case study in Brazil. Issue 4 (19th May 2021) - de Oliveira Alves, Lucas Bispo; Maeda, Shinnosuke; Morikawa, So; Kato, Hironori
ABSTRACT: This article investigates the influence of land titles on farmers' perceptions about the ease of conducting three types of land transactions: land sales, leases, and transfers by bequest. A questionnaire survey was conducted in a Brazilian municipality. Results indicate that farmers who have land titles perceive that land sales can be conducted more easily than those who do not have titles. However, perceptions regarding land leases and transfers as bequest were unaffected by the status of titling. This indicate that land titles may be ineffective in stimulating transaction types that are not part of local culture.